THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. MILLENIUM RATANINDO PERKASA - Prayoga, Dewa; Adiwati, Mei Retno (International Journal of Multidisciplinary Research and Literature, 2024)
This research is entitled the influence of organizational culture and work motivation on employee performance at PT. Millenium Ratanindo Perkasa which aims to find out how organizational culture and work motivation influence employee performance. This research method is quantitative and the population of this research is employees of PT. Millenium Ratanindo Perkasa. The sample collection method is non-probability sampling with a collection technique, namely purposive sampling, namely sampling based on criteria. The sample consists of 100 permanent production division employees. The analysis technique in this research uses the Partial Least Square (PLS) method. The results of this research prove that: (1) Organizational culture has a positive effect on employee performance. (2) Work Motivation has a positive effect on Employee Performance